Asymptomatic Bacteriuria in Pregnant Women in Outpatient Facilities - Maral G. Nogayeva; Svetlana A. Tuleutayeva (University Library System, University of Pittsburgh, 2015)
Urinary tract morbidity has increased by 7% in Kazakhstan between 2007 to 2011. Pregnant women with extragenital pathologies or kidney diseases had the greatest prevalence of morbidity. Asymptomatic bacteriuria (AB) is one of the most important risk factors of pyelonephritis development in pregnant women, and it can affect the course and outcome of pregnancy, delivery, and postnatal period. AB prevention requires prevention of pregnancy complications including early diagnostic of urinary tract infections, timely optimization of therapy at outpatient facilities, and dynamic follow-up.